Estimating the prevalence of dementia using multiple linked administrative health records and capture–recapture methodology - Michael Waller; Gita D. Mishra; Annette J. Dobson (Emerging Themes in Epidemiology, 2017)
Abstract Background Obtaining population-level estimates of the incidence and prevalence of dementia is challenging due to under-diagnosis and under-reporting. We investigated the feasibility of using multiple linked datasets and capture–recapture techniques to estimate rates of dementia among women in Australia. Methods This work is based on the Australian Longitudinal Study on Women’s Health. A random sample of 12,432 women born in 1921–1926 was recruited in 1996. Over 16 years of follow-up records of dementia were obtained from five sources: three-yearly self-reported surveys; clinical assessments for aged care assistance; death certificates; pharmaceutical prescriptions filled; and, in three Australian States only, hospital in-patient records. Results A total of 2534 women had a record of dementia in at least one of the data sources. The aged care assessments included dementia records for 79.3% of these women, while pharmaceutical data included 34.6%, death certificates 31.0% and survey data 18.5%. In the States where hospital data were available this source included dementia records for 55.8% of the women. Using capture–recapture methods we estimated an additional 728 women with dementia had not been identified, increasing the 16 year prevalence for the cohort from 20.4 to 26.0% (95% confidence interval [CI] 25.2, 26.8%). Conclusions This study demonstrates that using routinely collected health data with record linkage and capture–recapture can produce plausible estimates for dementia prevalence and incidence at a population level.